The Effect of Sex Education with Snakes and Ladders Methodtowards Knowledge of The Underwear Rule among First Grade Students of Kebonsari 1 Elementary SchoolTuban - kusno ferianto; hanim nur faizah (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2019)
Introduction: The Underwear Rule is a simple guide to help parents explain about sex education to children. The initial survey revealed that knowledge of The Underwear Rule among first grade students were still low. This research used one of methods of health promotion to increase knowledge of The Underwear Rule was snakes and ladders method. This method is fun and easy to play. The purpose of this research was to determine the effect of a snakes and ladders method towards knowledge of The Underwear Rule. Method: This research used pre-experimental design with pre and post test without control method. The samples were 51 respondents gathered by using simple random sampling technique. The independent variable was sex education with snakes and ladders method as intervention and the dependent variable was knowledge of The Underwear Rule was assessed by structured interview. Result and Analyzed: The research result revealed many of the respondents had fair knowledge in pre-test and almost all respondents had good knowledge in post-test, so H1 was accepted that mean there was effect of a snakes and ladders method towards knowledge of The Underwear Rule based on the analysis findings with the wilcoxon test in which ρ-value (0.000) ≤ α (0.05) was obtained. Discussion: The suggestion for school is expected to applied regularly sex education about The Underwear Rule with snakes and ladders method.